The Challenges and Countermeasures of Ideological and Political Education Theory Course Teaching for Art Students in Universities in the New Media Era - Liang, Jing; Zheng, Haoran (Journal of Education and Educational Technologies, 2023)
Contemporary art students in universities are a generation that has grown up in the context of new media. With the increasingly close integration of art and new media, in order to enable art students to better shoulder the mission of spreading the excellent culture of the Chinese nation, ideological and political course teachers in universities should strengthen the reform and innovation of ideological and political theory courses for art students in teaching content, teaching methods, and the use of new media, Ensure that art students embody a positive energy of thought in their artistic creation. In this study, a crude oil price prediction model based on quantum leap radius and polynomial fitting is established by building a market atom model, fitting financial funds as "market atoms" with energy, and applying quantum leap theory to describe the leaping behavior of price. The LSTM neural network model is used to learn the price jump paths of financial instruments to improve the prediction effect. After 2000 rounds of iterative training, the RMSE of the model reaches 3.1136, and the correlation coefficient is 0.48084; the model's loss function decreases rapidly, indicating that the training effect is good. The study reveals the potential value of quantum theory in finance, preliminarily verifies the application of quantum leap and LSTM model in crude oil price prediction, and provides new ideas for the in-depth study of quantum finance theory.